Elevated Kappa Index in the Absence of Cerebrospinal Fluid IgG Oligoclonal Bands: Contribution of Intrathecal IgM and IgA Synthesis - Krzysztof Smolik; Roberta Bedin; Patrizia Natali; Martina Cardi; Diego Franciotta; Anna Maria Simone; Paolo Immovilli; Mario Santangelo; Matteo Gastaldi; Giulia De Napoli; Francesca Vitetta; Diana Ferraro (Biomolecules)
The kappa index is a well-established marker of intrathecal synthesis (IS) of immunoglobulin (Ig). Routinely used for diagnostic aims, IgG IS, which can be assessed quantitatively (ad hoc formulas) or qualitatively (oligoclonal bands, OCBs), may fail in detecting a humoral immune response within the central nervous system (CNS). The main aim of this study was to evaluate the kappa index for its ability to detect the presence of CNS humoral immunity and to associate it with a distinct group of disorders, in the absence of IgG IS/OCBs. Within the kappa index-positive, IgG OCB-negative (Kappa+OCB-) patient group, we also examined whether IgM/IgA IS, determined with the IgM/IgA index and CSF IgM OCBs, could contribute to disease group stratification. Diagnoses were classified as multiple sclerosis (MS), or other inflammatory (INFL), infectious (INFECT), or non-inflammatory (Other) central/peripheral nervous system disorders. Sixty-nine Kappa+OCB- patients and 50 controls (24 Kappa-OCB- and 26 Kappa+OCB+ patients) were included in this study. The most frequent diagnosis in the Kappa+OCB- group was MS (27/69), followed by INFECT (16/69). Additional evidence of IS was demonstrated through an elevated IgG/IgM/IgA index or by the presence of IgM OCBs in 59%, and through only IgM/IgA IS in 52% of cases. In INFECT patients, the median IgM/IgA indexes were higher (p < 0.001) than in other groups, with 18 patients (95%) presenting an elevated IgM index, 11 patients (58%) presenting CSF IgM OCBs, and 10 patients (53%) presenting an elevated IgA index. The vast majority of all INFECT (16/19) belonged to the Kappa+OCB- group. Our data confirm that the kappa index performs at the highest level in assessing intrathecal humoral immunity and supporting the diagnosis of both MS and CNS infectious disorders, which are also characterized by the intrathecal production of IgM and IgA.